Construction of Self through Consumption by Young Sri Lankans: Extension of Cultural Self vs. Construction of Postmodern Self - Hewawasam, Buddhika; Wijetunga, Dinuka; ayakody, J.A.S.K.J. (My University, 2008)
Postmodernists argue consumption has become the prime determinant of the self-identity of Western consumers. Still Sri Lankan consumers appear to adhere to the traditional cultural values along with the Western consumption ethos. The study examined how Sri Lankan youth construct their self-identity through consumption and focused on whether Sri Lankan consumer is characterized by a strong cultural core or whether they are similar to the Western consumers. The study was done among a group of Sri Lankan youth belonging to two social classes and in-depth interview was used as the data collection method. Analysis was done using discourse analysis methodology. Researchers found that Sri Lankan consumers still adhere to a cultural core to a greater extent. The research contributes to empirical consumer research in Sri Lanka while introducing a latest qualitative research methodology. The research also challenges conventional marketing thought that exaggerates Western consumption ethos, and provides new understanding of the Sri Lankan consumers.